The Effect of Using Podcasts to Improve Listening Comprehension in Senior High School Students - Sitti Saum Sayidaturrahmah; Wa Ode Fatmawati; Desy Liliani Husain (Teknologi Pendidikan ID, 2024)
This study aims to investigate the effect of podcasts on students' listening comprehension before and after being taught to second grade students of SMA Negeri 2 Raha. The analysis results showed that the average pre-test score was lower than the post-test score. The N-Gain Test results showed that of all students, most students experienced moderate improvement, and only a handful of students experienced high improvement. The results of hypothesis testing showed that the alternative hypothesis was accepted with a significance value below the significance limit. Therefore, podcasts through the medium of Spotify can be useful for improving students' listening comprehension. The use of Spotify as a podcast platform allows it to be used in English language learning, especially in improving listening skills, pronunciation, and vocabulary.